The anther steps onto the stigma for self-fertilization in a slipper orchid. - Li-Jun Chen (Public Library of Science (PLoS), 2012)
Background Due to the spatial separation between male and female pollen grains from the anther of most flowering plants, including orchids, pollens are transported by wind or animals and deposited onto the receptive surface of the stigma of a different plant. However, self-pollination is common in pollinating animal-scarce habitats. In such habitats, self-pollinations require the assistance of a pollinating agent (e.g., wind, gravity, or floral assembly) to transport the pollen grains from the anther onto its own stigma. Methodology/principal findings Based on observations on floral morphology and flowering phenology, tests of the breeding system, and a comparison of pollination mechanisms, a new self-pollination process was discovered in the hermaphroditic (i.e., possessing spatially separated male and female organs) flower of a slipper orchid, Paphiopedilum parishii. The anther changes from a solid to a liquid state and directly steps onto the stigma surface without the aid of any pollinating agent or floral assembly. Conclusions The mode of self-pollination discussed here is a new addition to the broad range of genetic and morphological mechanisms that have evolved in flowering plants to ensure their reproductive success. The present self-contained pollination mechanism is a possible adaptation to the insect-scarce habitat of the orchid.